EMPLOYEE PERFORMANCE ANALYSIS OF SOCIAL REHABILITATION PAMARDI KHUSNUL KHOTIMAH TANGERANG SELATAN - Krisyanto, Edy (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study was to determine the effect of organizational culture, work ethic and discipline on the employees performance either partially or simultaneously of Social Rehabilitation Institution Pamardi Khusnul Khotimah at Tangerang Selatan. The results showed that organizational culture based on partial test was positive and significant effect on the performance of 76,2%, while work ethos can be good too was positive and significant effect on the performance of 72,2%, then work discipline also was positive and significant effect on the performance of 73%. The result of correlation coefficient (R2) of 76,7% can be summed up the effect of the variable X1 (organizational culture),  X2 (work ethos) and X3 (discipline) to variable Y (employees performance) where the relationship is positive. The results of calculation for 53.874 F-value further consultation with the F-table with dk = k numerator and denominator dk = (nk-1) with a 5% error level the importance of the F table = 2,80. Provisions applicable for F-value greater than F-table (53.874  > 2,80), it can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there is no effect between organizational culture, work ethos and discipline influence on employees performance is rejected, while the alternative hypothesis (Ha) is accepted